Extent and pattern of paracetamol usage for children and knowledge and attitude towards its usage among parents attending an outpatient clinic in Warangal district of Telangana - Nithisha, Thatikonda; Sharma, Sarita K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Paracetamol is the commonest available analgesic and antipyretic. It is readily accessed from pharmacy and provisional shops as over the counter drug, misuse of which can result in serious side effects like hepatic injury. The incidence of paracetamol overdose and toxicity is increasing today in India. However, there is little research published on same. So the present study was carried out to identify the extent and pattern of paracetamol usage for children and the knowledge and attitude of parents towards it. Methods: Present cross sectional study was carried out in an outpatient clinic in Warangal district of Telangana among 183 parents whose child had suffered from fever within one month of attending the clinic. Data was collected by interview technique using a pre tested questionnaire and analyzed using EPI INFO 7 3.5. Results: Out of 183 subjects, 156 (85.2%) had given paracetamol (single and combination) for fever. Of these156, 39 (25%) gave excess dose than permitted for the weight of the child. 105 (58%) had self medicated. The dosage per day was significantly more in self medicaters (p≤0.01). 36 (23%) had the misconception that paracetamol overdose does not cause liver toxicity. 128 (89%) of 143 subjects who gave incorrect dosage stated that it is not harmful to self administer and they advise others to self medicate. Conclusions: The knowledge of daily dosage and side effects of paracetamol is poor. The overall view is “self medication of paracetamol is not harmful”. This attitude of caregivers may pose a potential risk for paracetamol overdose unless they are educated.